The role of bile acid metabolism-related genes in prognosis assessment of hepatocellular carcinoma and identification of NPC1 as a biomarker - Xu, Maosen; Zhang, Yu; Tie, Yan; Luo, Yiqiao; Wang, Yang; Zhang, Ziqi (Frontiers in Endocrinology, 2025)
Hepatocellular carcinoma (HCC) is one of the most prevalent and deadly cancers worldwide, with a high recurrence rate and poor prognosis. Understanding the molecular mechanisms driving HCC progression is crucial for improving prognostic accuracy and developing targeted therapies. Bile acids (BAs), as critical regulators of liver metabolism and inflammation, have recently been implicated in tumorigenesis and cancer progression. In particular, bile acids metabolism (BAM)-related genes play a pivotal role in the regulation of cellular proliferation, apoptosis, and immune responses in HCC. In this study, we explored the prognostic significance of BAM-related genes in HCC. Using a comprehensive bioinformatics approach, we analyzed transcriptomic data from public databases, identifying 111 differentially expressed BAM-related genes associated with patient survival. We then constructed a prognostic model based on these key genes, utilizing multivariate Cox regression analysis to determine their independent predictive value for overall survival in HCC patients. We identified four key BAM-related genes including AKR1D1, CYP7A1, FABP6, and NPC1 as significant prognostic markers. Among these genes, only NPC1 was the highly expressed gene and demonstrated statistically difference between HCC and normal liver tissues. The downregulation of NPC1 inhibited HepG2 cell proliferation, migration, and invasion. In conclusion, BAM-related genes offer a promising avenue for improving prognosis assessment in HCC patients. Our findings highlight the potential of NPC1 as a valuable tool for risk stratification and personalized treatment strategies in HCC patients.